Experimental investigation on the mobility reduction factor of surfactant-alternating-gas foam flooding - Hematpour, H. (University of Kuwait, 2019)
This study investigates the effect of different existing parameters in current foam models on SAG foam process. Foam flooding is a common Enhanced Oil Recovery (EOR) method to mitigate the drawbacks of the gas injection process. Whereas Surfactant-Alternating-Gas (SAG) is a common technique in real cases, all developed foam flow models have been established based on pre-generated foam flooding. In this study, a set of core flooding experiments were designed to meet the objective. These experiments considered the effect of several parameters on the mobility reduction factor (MRF). The parameters included surfactant types, flow rate, surfactant concentration, and salinity. A high permeable core was considered as the porous medium, three different anionic surfactants (AOS, IOS and MFOAMX) were employed as the foaming agents, and the injected gas was nitrogen. The results were interpreted the SAG foam process. The results show that surfactant concentration plays an imperative role in MRF, but the salinity effect is not significant. Â© 2019 University of Kuwait. All rights reserved.